Use of body surface area in rural buffaloes - GOKHALE, S B; SHIRSATH, T V; SONAWANE, D R; SHINDE, D N (The Indian Journal of Animal Sciences, 2017)
The study on 919 rural Murrah adult buffaloes aging between 39 to 89 months belonging to 846 farmers spread in 555 villages of 5 districts in Uttar Pradesh was conducted to estimate body surface area (BSA) using 2D photographic image by digital camera and using computer software BIOVIS PSM_L1000. Mean BSA was 2.92±0.16 sq. m. Effect of district, body condition and age of animal was not significant while animal body size and profession of buffalo keeper were found to have important effect on the BSA of animal. Mean body length, height at withers, chest girth and estimated body weight were 98.73±0.44 cm, 126.81±0.44 cm, 152.64±0.64 cm and 220.03±0.02 kg, respectively. Correlations between different body measurements studied and BSA were highly significant and ranged from 0.500±0.03 to 0.993±0.03 indicating their utility at field level for selecting traits effective in strategizing breeding programs in districts of eastern Uttar Pradesh region.